Applied Optimization
DOI: 10.1007/0-387-26771-9_4
|View full text |Cite
|
Sign up to set email alerts
|

On Complexity of Stochastic Programming Problems

Abstract: The main focus of this paper is in a discussion of complexity of stochastic programming problems. We argue that two-stage (linear) stochastic programming problems with recourse can be solved with a reasonable accuracy by using Monte Carlo sampling techniques, while multi-stage stochastic programs, in general, are intractable. We also discuss complexity of chance constrained problems and multi-stage stochastic programs with linear decision rules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
197
0
9

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(212 citation statements)
references
References 51 publications
6
197
0
9
Order By: Relevance
“…Whereas a stochastic optimization approach addresses the issue of uncertain parameters, it is by and large computationally intractable. Shapiro and Nemirovski [21] give hardness results for two-stage and multistage stochastic optimization problems where they show that multistage stochastic optimization is computationally intractable even if approximate solutions are desired. Furthermore, to solve a two-stage stochastic optimization problem, Shapiro and Nemirovski [21] present an approximate sampling based algorithm where a sufficiently large number of scenarios (depending on the variance of the objective function and the desired accuracy level) are sampled from the assumed distribution and the solution to the resulting sampled problem is argued to provide an approximate solution to the original problem.…”
mentioning
confidence: 99%
“…Whereas a stochastic optimization approach addresses the issue of uncertain parameters, it is by and large computationally intractable. Shapiro and Nemirovski [21] give hardness results for two-stage and multistage stochastic optimization problems where they show that multistage stochastic optimization is computationally intractable even if approximate solutions are desired. Furthermore, to solve a two-stage stochastic optimization problem, Shapiro and Nemirovski [21] present an approximate sampling based algorithm where a sufficiently large number of scenarios (depending on the variance of the objective function and the desired accuracy level) are sampled from the assumed distribution and the solution to the resulting sampled problem is argued to provide an approximate solution to the original problem.…”
mentioning
confidence: 99%
“…Let (x, r) be a feasible solution to the LP relaxation of (21). Observe that for each element e ∈ U , we either have S:e∈S x S ≥ 1/2 or S:e∈S r A,S ≥ 1/2 for every scenario A that contains e. Now, define:…”
Section: Covering Problemsmentioning
confidence: 99%
“…Under some mild assumptions, it has been shown [14,21] that the optimal value of (2) is a good approximation to that of (1) with high probability, and that the number of samples N can be bounded. Unfortunately, the bound on N depends on the maximum variance V (over all x ∈ X) of the random variables q(x, ω), which need not be polynomially bounded by the input size.…”
mentioning
confidence: 99%
“…As was pointed out in [43], solving and analyzing the SAA counterparts for multistage stochastic models seem to be very hard in general. Instead of solving the SAA counterpart of the multiperiod model, we propose a dynamic programming framework that departs from previous sampling-based algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Kleywegt, Shapiro and Homem-De-Mello [24], Shapiro and Nemirovski [43] and Shapiro [40] have considered the SAA in a general setting of two-stage discrete stochastic optimization models (see [35] for discussion on two-stage stochastic models). They have shown that the optimal value of the SAA problem converges to the optimal value of the original problem with probability 1 as the number of samples grows to infinity.…”
Section: Introductionmentioning
confidence: 99%